2017
DOI: 10.1108/ijm-12-2015-0235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of information quality of employment website on attitude toward the website

Abstract: Purpose The purpose of this paper is to develop and validate an empirical model examining the job seekers’ perception about information quality of corporate employment websites and its impact on their attitude toward the websites through perceived playfulness and usefulness. Furthermore, the study also examines the job seekers’ e-trust as condition under which these mechanisms generate website attitude. Design/methodology/approach A sample of 385 active job seekers was selected through systematic random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…It is additionally clear that consumer loyalty prompts buy aim. In his investigation Priyadarshini C et al, found that consumer loyalty unequivocally influenced purchase aim along these lines supporting our perceptions [18]. Weber A. N and Badenhorst Weiss J.A found that data given by an online store altogether influenced consumer loyalty [25].…”
Section: Conclusion and Future Researchsupporting
confidence: 73%
See 1 more Smart Citation
“…It is additionally clear that consumer loyalty prompts buy aim. In his investigation Priyadarshini C et al, found that consumer loyalty unequivocally influenced purchase aim along these lines supporting our perceptions [18]. Weber A. N and Badenhorst Weiss J.A found that data given by an online store altogether influenced consumer loyalty [25].…”
Section: Conclusion and Future Researchsupporting
confidence: 73%
“…Besides, e-trust was found to direct the above said connections [18]. This examination means to look at determinants of saw site quality and relationship among outcomes of saw site quality.…”
Section: Review Of Literaturementioning
confidence: 93%
“…Similarly, Lin (2010) found that perceived usefulness had a significant effect on attitude towards intention to use e-recruitment system. Results of another study by Priyadarshini et al (2017) indicated that the information quality dimensions positively influence perceived usefulness, and perceived usefulness subsequently affects attitude towards a website.…”
Section: Perceived Usefulness Behavioral Intention To Use E-recruitmentmentioning
confidence: 98%
“…A good web design can attract internet users and make internet users come back to visit the website (King, R. C., et al, 2016). When creating a good website, several important points can be needed, such as Usability, Navigation System, Visual Design, Content, Compatibility, Length of Process, Functionality, Accessibility, and Interactivity (Priyadarshini, C., et al, 2017). In the website's current development, many web design views can be said to have not met the requirements for designing a good and correct website.…”
Section: Introductionmentioning
confidence: 99%